Effect of plane of nutrition on haematobiochemical constituents and serum enzyme activity in sheep infected with Haemonchus contortus - DUBEY, C S; MONDAL, B C; TIWARI, D P; KUMAR, ANIL; YADAV, C L (The Indian Journal of Animal Sciences, 2011)
Adult Muzaffarnagari sheep (18) of 11â€“13 months of age infected with Haemonchus contortus were divided into 3 groups of 6 animals each, and were fed 3 levels of concentrate mixture (groundnut cake and wheat bran in 70:30 ratio), i.e. low plane (200 g concentrate), medium plane (300 g concentrate) and high plane (400 g concentrate) to groups 1, 2 and 3, respectively, along with ad lib. mixed green fodder (green maize and grasses) to each animal for 90 days. Blood samples were collected from each animal on 0, 30th, 60th and 90th day post-feeding to see the effect of plane of nutrition on haematobiochemical constituents in sheep infected with Haemonchus contortus. The total serum protein, albumin and globulin concentrations in different groups were similar. The sheep in group 1 showed significantly higher blood glucose level in comparison to group 3, however, on 30th day it was also significantly higher in group 2 than that in group 3. The blood cholesterol and haemoglobin levels did not differ significantly in sheep fed different planes of nutrition although packed-cell volume in groups 2 and 3 was significantly higher than that in group 1 on 60th day of feeding. There was no significant difference in packed-cell volume between groups 2 and 3. The overall mean serum glutamate oxaloacetate transaminase (SGOT) and serum glutamate pyruvate transaminase (SGPT) activities were significantly higher in sheep of groups 2 and 3 than that in group 1 but there were no differences between groups 2 and 3. The serum pepsinogen and alkaline phosphatase activities were not affected in sheep due to different planes of nutrition. The overall mean faecal egg counts were significantly lower in groups 2 and 3 than that in group 1. It is concluded that protein rich diet leads to reduced establishment and fecundity of the worms in sheep infected with Haemonchus contortus. Â